2021
DOI: 10.3390/educsci11060290
|View full text |Cite
|
Sign up to set email alerts
|

Using Videos in Blended E-Learning for a Structural Steel Design Course

Abstract: Conventional methods of teaching structural engineering topics focus on face-to-face delivery of course materials. This study shows that using video-based e-learning in delivering an undergraduate Structural Steel Design course satisfactorily achieved most of the course learning outcomes. Video-based e-learning with animations and simulations gives students a profound understanding of the course intricate design materials. To gauge the effectiveness of video-based e-learning of the course, an online evaluation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
10
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 65 publications
2
10
0
1
Order By: Relevance
“…Previous research has shown that videos are one of the potential and effective educational tools (El-Ariss et al, 2021; Robertson & Flowers, 2020). Video-based learning enhances the students’ engagement, learning performance, and motivation (Scagnoli et al, 2017) and encourages self-directed and autonomous learning (van der Meij & Dunkel, 2020).…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous research has shown that videos are one of the potential and effective educational tools (El-Ariss et al, 2021; Robertson & Flowers, 2020). Video-based learning enhances the students’ engagement, learning performance, and motivation (Scagnoli et al, 2017) and encourages self-directed and autonomous learning (van der Meij & Dunkel, 2020).…”
Section: Literature Reviewmentioning
confidence: 99%
“…In order to increase the effectiveness of IVs, the theories such as the cognitive theory of multimedia learning (Mayer, 2009) and cognitive load theory (Sweller, 1994) may be a guide for educators and educational technologists. However, typically, online IVs lack the elements of interaction and feedback mechanisms (El-Ariss et al, 2021). Hence, researchers have recently focused on the interaction and feedback elements in video-based learning.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Other digital resources used in learning such as videoreality or virtual reality videos provide opportunities to create a better learning process [9], [10], and have a positive impact on students' attitudes and self-regulated learning [8]. The study done by EL-Ariss et al [29] believe that the use of video in blended elearning can increase students' in-depth understanding. Another finding revealed that there was a positive attitude towards learning videos, the reason is because it can support active learning, increase learning motivation and student engagement, learning with videos is fun [30].…”
Section: Literature Reviewmentioning
confidence: 99%
“…Melalui video podcast peserta didik dapat merasa nyaman ketika akses dari rumah, dapat memungkinkan untuk memutar ulang video untuk mencari informasi, membuat catatan, mengkonfirmasi isu-isu yang diterima serta menguatkan informasi-informasi yang penting. Banyak siswa lebih menyukai melihat video podcast di rumah agar lebih konsentrasi dalam proses pembelajaran (El-Ariss et al, 2021;Hill & Nelson, 2011).…”
Section: Hasil Penelitian Dan Pembahasanunclassified